2020
DOI: 10.24135/pacifichealth.v3i0.44
|View full text |Cite
|
Sign up to set email alerts
|

Our people, our food, our planet

Abstract: Video link: Our people, our food, our planet: Sustainable food systems policy in the Pacific Pacific Island Countries and Territories are facing a health crisis with non communicable diseases (NCDs) currently accounting for more than 80% of deaths. In the 21st century, advances in health intervention and policy render this figure unacceptable. Multiple risk factors contribute to the NCD crisis; a leading driver being obesity due to changing dietary practices arising from the global food system. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Nutrition transition is the concept used in the literature to describe the evolving dietary patterns within societies, marked by a shift from traditional, locally sourced diets to more processed and ultra-processed foods and beverages, which are less nutrient dense and high in deleterious nutrients, such as saturated fat, added sugar and salt [3][4][5]. The nutrition transition has also been accompanied by lifestyle changes, including less physical activity and loss of farming practices as a result of urbanisation [6]. This shift has implications for public health, particularly the increased risk for non-communicable diseases (NCDs).…”
Section: Introductionmentioning
confidence: 99%
“…Nutrition transition is the concept used in the literature to describe the evolving dietary patterns within societies, marked by a shift from traditional, locally sourced diets to more processed and ultra-processed foods and beverages, which are less nutrient dense and high in deleterious nutrients, such as saturated fat, added sugar and salt [3][4][5]. The nutrition transition has also been accompanied by lifestyle changes, including less physical activity and loss of farming practices as a result of urbanisation [6]. This shift has implications for public health, particularly the increased risk for non-communicable diseases (NCDs).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, there is substantial agreement that nutrition transitions from traditional plant and seafood-based diets to diets high in processed, imported foods are at the core of the obesity epidemic in PICs. Imported foods, predominantly food products high in unhealthy meat, salt, sugar and unhealthy fats, now constitute 60-100% of the food supply across the region [5][6][7][8][9][10]. Comparisons of data between national nutrition surveys undertaken in the early 2000s and 8-11 year follow-up surveys indicate that fruit and vegetable consumption in PICs is low [11,12] and decreasing in some PICs, including Tonga, Tokelau, Solomon Islands and Nauru [12].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, one modelling exercise undertaken on Solomon Islands suggested that a 40% tax on SSBs would directly reduce type 2 diabetes in the population by up to 24,000 cases, and any taxation policy raising consumer costs by 20% or more would significantly reduce consumption of these products [20]. Given these potential beneficial effects, fiscal policies have been a key consideration at national and regional PIC discussions of NCD-related interventions over the last two decades [5,21].…”
Section: Introductionmentioning
confidence: 99%